2016
DOI: 10.1021/acs.nanolett.6b03208
|View full text |Cite
|
Sign up to set email alerts
|

Blue Phosphorene Oxide: Strain-Tunable Quantum Phase Transitions and Novel 2D Emergent Fermions

Abstract: Tunable quantum phase transitions and novel emergent fermions in solid state materials are fascinating subjects of research. Here, we propose a new stable two-dimensional (2D) material, the blue phosphorene oxide (BPO), which exhibits both. Based on first-principles calculations, we show that its equilibrium state is a narrow-bandgap semiconductor with three bands at low energy. Remarkably, a moderate strain can drive a semiconductor-to-semimetal quantum phase transition in BPO. At the critical transition poin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 57 publications
(100 reference statements)
4
112
0
Order By: Relevance
“…However, for bilayer graphene, there are two such points at BZ corners related by the time reversal symmetry; whereas for ML Na 2 O, there is only one double Weyl point sitting at the BZ center. The double Weyl point endows ML Na 2 O with an interesting optical property, i.e., it should exhibit a universal optical absorbance of πα ≈ 2.3% (α is fine‐structure constant) at low frequencies [for ℏω < ( M 2 – M 1 ) here] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for bilayer graphene, there are two such points at BZ corners related by the time reversal symmetry; whereas for ML Na 2 O, there is only one double Weyl point sitting at the BZ center. The double Weyl point endows ML Na 2 O with an interesting optical property, i.e., it should exhibit a universal optical absorbance of πα ≈ 2.3% (α is fine‐structure constant) at low frequencies [for ℏω < ( M 2 – M 1 ) here] …”
Section: Resultsmentioning
confidence: 99%
“…Currently, a target in this direction is to explore new types of band degeneracy points and the associated new emergent fermions. For example, previous works have theoretically proposed 2D massive Dirac fermions, double Weyl fermions, and pseudospin‐1 fermions in some 2D materials, such as blue phosphorene oxide and monolayer (ML) Mg 2 C . However, these proposed materials are not ideal because the emergent fermions are not realized in their equilibrium states.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 2D quadratic band-touching points have been found in bilayer graphene 59 and in blue phosphorene oxide 60 . It will be interesting to explore these exotic band degeneracy points and their novel physics in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…and solid-state materials 48 . For massless spin-1 fermion systems without gaps, QHEs have been investigated and it has been found that each spin-1 point contributes an integer Hall conductance 39 .…”
mentioning
confidence: 99%